The Influence of Dhikr Psychoreligious Therapy on Anxiety Levels of Hernia Pre Surgery Patients - Miftakurrosyidin Miftakurrosyidin; Dwi Nur Aini; Priharyanti Wulandari (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
It is estimated that each year there are 230 million surgeries performed worldwide. The most common response experienced by preoperative patients is a psychological response related to anxiety. Non-pharmacological management of preoperative anxiety hernia with one type of distraction, namely Dhikrpsychoreligius therapy. Quantitative research using pre-experimental type with a one-group pretest-posttest design without control group design. The sampling technique was purposive sampling with a total of 36 respondents. The data obtained by using the Wilcoxon Signed Rank Test. Based on the Wilcoxon Signed Rank Test, it was found that the pre-test-post-test changes with the results of the Sign value. 0.00> 0.05, so that Ho is rejected and Ha is accepted. There is an effect of Dhikrpsychoreligious therapy on the level of anxiety of preoperative hernia patients in the bay room of RSI Sultan Agung Semarang.